Saint Benedict, Montecassino, and the crisis of ninth-century southern Lombards in early medieval Cassinese memory
1 online resource.
Keywords: "The dissolution of the Lombard political unity in southern Italy and the Muslim military activities in that area rendered the ninth century a crucial, yet troubled period for the history of this part of the Italian peninsula. The abbey of Montecassino was deeply affected by those events as well. Its riches, in fact, made it an easy target for the Muslims, who, after imposing heavy tributes on the monastery, pillaged and destroyed it in 883. Several years had to pass before Saint Benedict's monks could return to Montecassino. In the difficult period of exile they put a lot of effort in the reconstruction of their community's identity as well as in reaffirming its role as repository of southern Italy's memory. In this process of reconstruction the texts known as The Chronicles of Saint Benedict of Cassino had the fundamental task of describing as well as explaining the events that had provoked the crisis of southern Lombard Italy. Using a topical approach and presenting the English translation and the Latin text of excerpts from The Chronicles of Saint Benedict of Cassino, this volume examines how the Cassinese historians narrated that tragic period and at the same time mentioned the glorious times of Saint Benedict's foundation of Montecassino. Saint Benedict, Montecassino, and the Crisis of Ninth-Century Southern Lombards in Early Medieval Cassinese Memory will appeal to scholars and students of early medieval southern Italy, as well as all those interested in medieval Europe and the medieval Mediterranean"-- Provided by publisher.